The young scientist book of archaeology - Cork, Barbara; Reid, Struan; Ashman, Ian. (London ; Tulsa, Okla. : Usborne : EDC [distributor], 1984)
Explains how detective work and the latest scientific techniques are used to piece together the clues about how people lived in the past.
5.0
5-8
Keywords: Archaeology -- Juvenile literature; Archaeology; Archeology